Structural, biochemical and inhibition studies on hypoxia-inducible factor (HIF) prolyl hydroxylases - Lippl, K (2018)
In humans and other animals, the chronic hypoxic response is mediated by the hypoxia-inducible transcription factors (HIFs), which regulate the expression of genes that counteract the effects of limiting oxygen. HIF prolyl hydroxylases (PHDs) regulate cellular levels and transcriptional activity of HIFs by catalysing the post-translational hydroxylation of conserved prolyl residues in the HIFα subunits. Based on structural and biophysical studies, it has been proposed that the three human PHDs (PHD1-3) act as oxygen sensors, providing a direct link between cellular oxygen availability and the regulation of the hypoxic response. Work in this thesis has focused on the in vitro characterisation of the human HIF prolyl hydroxylases and the PHD from the simplest existent animal, Trichoplax adhaerens. Previous studies on human PHDs suggested that they are not selective for their well established HIF substrates, but accept additional substrates other than HIFs. With PHD inhibitors currently in late- stage clinical trials for treatment of anaemia, investigating the validity of the proposed promiscuous nature of human PHDs is of major medicinal relevance. In systematic and detailed studies, reported non-HIF substrates were probed for reaction with PHDs, using various mass spectrometric and NMR-based approaches. No evidence was found for PHD-catalysed hydroxylation of non-HIF substrates in the studies presented in this thesis, suggesting that PHDs might be more selective for their HIF substrates than previously perceived. Inhibition studies were carried out on human PHD1-3, to characterise currently available PHD inhibitors, including such as used in clinical trials. In addition, a series of new PHD inhibitors was tested, and a proof of concept was provided that inhibitors capable of discriminating between PHD2 and PHD3 can be developed. Structural and biochemical studies on human PHD2 variants were performed. As a result, functional relationships between clinically observed mutations in the EGLN1 gene encoding for PHD2 and disease phenotypes, such as cancer and erythrocytosis, were established. Finally, work was concentrated on the evolution of the HIF pathway in animals and beyond. To investigate if the HIF prolyl hydroxylase in T. adhaerens (TaPHD) is capable of sensing hypoxia in a similar way as human PHD2, a comparative biochemical characterisation of TaPHD and human PHD2 was performed. Strong evidence was provided that the special kinetic properties of human PHD2 are conserved in TaPHD, including unusually high Km values for oxygen, low substrate uncoupled 2OG turnover, and structural elements in the active sites of human PHD2 and TaPHD, which enable the unusually slow reaction of human PHD2 with oxygen. Further, evolutionary links between human HIF prolyl hydroxylases and Skp1-mediated oxygen-sensing mechanisms in lower organisms, such as Dictyostelium discoideum and Toxoplasma gondii, were investigated. Overall, the work described in this thesis provided new insights into the substrate selectivity of human PHDs, and their potential for therapeutic manipulation. A high degree of conservation between PHDs ranging from humans to T. adhaerens was revealed, highlighting the importance of HIF-mediated hypoxia sensing as a prerequisite for the evolution of higher animals.